Loss of Histone H3 Methylation at Lysine 4 Triggers Apoptosis in Saccharomyces cerevisiae - Walter, David (Public Library of Science, 2014)

(untitled)
Monoubiquitination of histone H2B lysine 123 regulates methylation of histone H3 lysine 4 (H3K4) and 79 (H3K79) and the lack of H2B ubiquitination in Saccharomyces cerevisiae coincides with metacaspase-dependent apoptosis. Here, we discovered that loss of H3K4 methylation due to depletion of the methyltransferase Set1p (or the two COMPASS subunits Spp1p and Bre2p, respectively) leads to enhanced cell death during chronological aging and increased sensitivity to apoptosis induction. In contrast, loss of H3K79 methylation due to DOT1 disruption only slightly affects yeast survival. SET1 depleted cells accumulate DNA damage and co-disruption of Dot1p, the DNA damage adaptor protein Rad9p, the endonuclease Nuc1p, and the metacaspase Yca1p, respectively, impedes their early death. Furthermore, aged and dying wild-type cells lose H3K4 methylation, whereas depletion of the H3K4 demethylase Jhd2p improves survival, indicating that loss of H3K4 methylation is an important trigger for cell death in S. cerevisiae. Given the evolutionary conservation of H3K4 methylation this likely plays a role in apoptosis regulation in a wide range of organisms.